2007
DOI: 10.1007/s00125-007-0848-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin secretion, glucokinase gene transcription and beta cell proliferation by adipocyte-derived Wnt signalling molecules

Abstract: Aims/hypothesis Adipocytes secrete signalling molecules that elicit responses from target cells, including pancreatic beta cells. Wnt signalling molecules have recently been identified as novel adipocyte-derived factors. They also regulate insulin secretion in pancreatic beta cells and the cell cycle. The aim of this study was to investigate the effect of adipocyte-derived Wnt signalling molecules on insulin secretion and beta cell proliferation. Methods Human adipocytes were isolated to generate fat cell-cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 49 publications
7
92
1
4
Order By: Relevance
“…There is strong evidence that the Wnt signalling pathway regulates prenatal and postnatal beta cell development in mice as well as glucose sensing in pancreatic beta cells [27,28]. Also, the activation of Wnt signalling in beta cell lines or in isolated islets has been shown to enhance beta cell proliferation [10,[29][30][31]. Thus, increased β-catenin levels in islets caused an expansion of beta cell mass, whereas the depletion of TCF7L2 reduced proliferation in human islets [10,30].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that the Wnt signalling pathway regulates prenatal and postnatal beta cell development in mice as well as glucose sensing in pancreatic beta cells [27,28]. Also, the activation of Wnt signalling in beta cell lines or in isolated islets has been shown to enhance beta cell proliferation [10,[29][30][31]. Thus, increased β-catenin levels in islets caused an expansion of beta cell mass, whereas the depletion of TCF7L2 reduced proliferation in human islets [10,30].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies implicated β-cell dysfunction as the underlying cause of diabetes in patients with the TCF7L2 risk variant [2][3][4][5] and have suggested that Wnt signalling plays an important role in both pancreatic development and in the function of mature pancreatic islets [6]. The activation of the canonical Wnt pathway, by ligands such as Wnt3a, has been of particular interest as it can increase β-cell proliferation, decrease apoptosis and improve glucose stimulated insulin secretion [6][7][8][9][10][11][12]. However there is now increasing evidence that non-canonical Wnt ligands such as Wnt4 can antagonise the signalling mediated by Wnt3a and may play an equally important role in β-cell function [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The underlying defect is most probably impaired sensing of glucose by the affected beta cells [6]. In line with this, molecular studies indicate co-activation of the gene encoding glucokinase-a major regulator of glucose-sensing in beta-cells-by β-catenin [3]. In addition, knocking down the gene encoding TCF7L2 in adult murine and human islets in vitro reduces beta cell proliferation and insulin secretion [7], emphasising the importance of this transcription factor for beta cell function.…”
Section: Frpmentioning
confidence: 75%
“…1a) [2]. WNT-signalling molecules are expressed on murine and human beta cells and WNT signalling has recently been identified as a regulator of beta cell proliferation and insulin secretion in vitro and in animal studies [3,4].…”
Section: Frpmentioning
confidence: 99%
See 1 more Smart Citation